ANALISIS YURIDIS SIFAT MELAWAN HUKUM MATERIIL DALAM FUNGSINYA YANG NEGATIF TERHADAP PENGGUNAAN GANJA UNTUK PENGOBATAN KISTA/ SYRINGOMYELIA (PUTUSAN NOMOR 111/PID.SUS/2017/PN.SAG) - Sahetapy, Refly Adidjasa; Rahaditya, R (Jurnal Hukum Adigama, 2021)
Indonesian criminal law recognizes several reasonsâ€œthat can beâ€used as a basis forâ€a judge in imposing a criminal sentence or sentence on a defendant who has been brought to court for committing a criminal act. The reasons that are used as the basis by the judge are named as excuses for criminal offenses. The reasonâ€for the annulment of punishment is addressed to the judge, to determine under whatâ€conditions a personâ€who commits a criminal act or fulfills the formulation of offense or â€œbestanddelenâ€ can or cannot be convicted. One of theâ€œreasons for the eradication of crime is the nature of violatingâ€œthe material law in its negative function which means that even though the act fulfills the element of offenseâ€but does not conflict with the sense of justice of the community, the act is not punished. The theory should be used and taken into consideration by the Panel of Judges in the case that the author adopted, namely the Defendant was charged with using Article 116 paragraph (1) of Law Number 35 of 2009 concerning Narcotics because the Defendant gave marijuana to his wife who was suffering from spinal cysts / Syringomyelia as an act This is not an act that is disgraceful or contrary to the sense of justice of society, the act is not an anti-social act, namely that the essence of a criminal act is an anti-social act, furthermore that the Defendant is not consuming marijuana is proven by negative test results, the Defendant also did not gain or trade marijuana, or used marijuana to others for profit. so that the author is of the opinion that the defendant should be able to be released, if the panel of judges uses the theory of nature against material law in its negative function as a consideration in deciding the case.